Penentuan Waktu Saat Lalu Lintas Dari Rekaman Foto Terestris Dengan Kamera Nonmetrik - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
The existing condition of the street and the increasing of the vehicle is not proportional, therefore the traffic is too heavy. This research tries to determine the heaviest traffic moment by means of the terrestrial photographs. The sample of the research was taken at locations of the path of the streets in Kotamadia Yogyakarta. The photography were taken periodically in every hour from 7.00 o'clock AM to 17.00. There four day groups, Monday to Tuesday was one group